PROSPECTS FOR THE DEVELOPMENT OF THE ORGANIC MARKET IN UKRAINE IN THE CONTEXT OF THE EUROPEAN GREEN DEAL - Іnna Honcharuk; Roman Lohosha; Dina Tokarchuk (Baltic Journal of Economic Studies)
The successful process of Ukraine's European integration is contingent on the rapid development of a new market segment: namely, organic products. This is regarded as a means of increasing the competitiveness of Ukraine's agricultural sector. Concurrently, the production of organic products assumes particular relevance when the state is expected to create conditions for the export of organic agricultural products to the EU. The article is aimed at studying the problems and prospects for the development of the organic market in Ukraine in the context of the European Green Deal. The methodological approach combines a comprehensive review of scientific literature, analysis of industry reports and case studies to assess the development of the organic market in Ukraine. According to the results of the study, Ukraine, following global trends, is gradually focusing on the development of various green sectors of the agri-food system, in particular, the production of organic agricultural products. The development of the organic market is based on organic farming. The area of land under organic farming in countries around the world is gradually increasing in parallel with the introduction of the latest technologies (sensor networks, control of soil moisture, soil temperature, CO2 levels, etc.). At the same time, the number of organic producers is growing both in Ukraine and around the world. Organic products are becoming increasingly attractive to both European and national consumers. In Ukraine, the organic segment of the market is actively developing, as evidenced by the positive dynamics of the agricultural sector. However, a significant share of organic production is carried out uncertified, often without proper regulation. This makes it difficult to monitor this sector, which is mostly composed of farms and private households. Over time, the integration of such farms into the monitoring network will become necessary in the process of formalising the organic market, as the lack of certification limits prices and economic returns. Despite the challenges, including a full-scale war, Ukraine has preserved its organic sector, diversified production and attracted new players to the organic market. Reaffirming its focus on European integration, Ukraine has identified the strategic adaptation of its national organic legislation to EU norms as a key priority. For Ukraine, as an EU partner country, the European Green Deal creates additional opportunities for the development of the organic market. In addition, the European Union supports farmers who implement organic practices through subsidy and financing programmes, which can be an incentive for Ukrainian organic producers. The study found that the domestic market for organic products requires the creation of a modern infrastructure. At the same time, the domestic market of Ukraine remains under the influence of unregulated pricing mechanisms, which leads to overpricing and lack of stable demand for organic products. Further research in this area should focus on the peculiarities of the formation and development of the organic market in Ukraine, in particular from the perspective of small businesses in the context of European integration.